Comparing the Effect of Aromatherapy with Salvia officinalis and Topical Lidocaine Gel on Pain Intensity During Insertion of Vascular Catheters in Hemodialysis Patients - bahareh nikraftar; Mahdi Basiri Moghadam; Mohammad Mojalli (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Hemodialysis is a common treatment for end-stage renal failure, and cannulation causes considerable pain. Topical lidocaine gel and aromatherapy as a complementary medicine are used to relieve the pain. Aromatherapy is associated with fewer side effects than medication, so, the present study was conducted to compare the effect of aromatherapy with Salvia officinalis and topical lidocaine gel on pain intensity during insertion of vascular needles in patients undergoing hemodialysis. Materials and methods: A clinical trial with before and after study design was conducted. Sampling was done using convenience sampling and 23 patients were selected and studied at three stages: pre-intervention, intervention I (topical lidocaine gel 2%, 2 mll or 2 gr in an area of 5 cm2 over the fistula), and intervention II (aromatherapy with 3 drops of leaf extract of S. officinalis 10%). Pain intensity was measured by visual analogue scale and data were analyzed in SPSS V 14.5 applying repeated measures ANOVA. Results: Mean scores for pain intensity were 6.09±1.28, 4.30±2.36, 4.13±1.98 at pre-intervention, intervention I, and intervention II phases, respectively. LSD Post-Hoc test showed significant differences in mean scores for pain intensity between pre-intervention and the two intervention phases (P<0.001), while these phases were not found to be significantly different in mean scores for pain intensity (P=0.7). Conclusion: According to this study, the aroma of S. officinalis could be used in reducing pain before insertion of vascular needles in patients undergoing hemodialysis.